論人體胚胎研究“軟法”修改之正當性: On the Legitimacy of Amending the “Soft Law” of Human Embryo Research - DING, Chunyan (International Journal of Chinese & Comparative Philosophy of Medicine, 2021)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. This commentary briefly discusses the substantive and procedural justifications for amending the longstanding 14-day rule, a soft-law limitation on the culturing of human embryos. The 14-day rule was established on the basis of general recognition of the human embryo's special status, accompanied by widespread public conversation and engagement. In principle, amending this rule would require the same substantive and procedural justifications. However, such justifications were absent prior to the lifting of the rule by the ISSCR in its 2021 guidelines. This article also discusses the value and importance of the 14-day rule to the development of human embryo research in the last three decades. Discarding the rule without the proper substantive and procedural justifications is likely to damage public trust and confidence in future human embryo research.